2020
DOI: 10.3390/app10196963
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable-Milk-Based Yogurt-Like Structure: Rheological Properties Influenced by Gluten-Free Carob Seed Flour

Abstract: There is a constant increase in the attention being paid to food quality and the effects of food on human health among consumers. Vegetable milk is among the foods whose consumption worldwide has increased because, when compared to animal-derived milk, it offers numerous benefits for human health. The aim of this research work was to use vegetable milk to obtain yogurt-like products enriched with different concentrations of carob seed flour, which has a double function: to modify, and thus perfect, the rheolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Our results demonstrated that the storage modulus was significantly higher ( p < 0.05) for 16-A than 12-A ( Figure 1 c). Higher TS levels resulted in more solid particles in the system, which resulted in an increase in the number of intermolecular interactions and the formation of a stronger network structure, thus leading to a higher storage modulus [ 54 ]. Further, it can be observed that the higher loss modulus was also exhibited by 16-A than 12-A ( Figure 1 d).…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrated that the storage modulus was significantly higher ( p < 0.05) for 16-A than 12-A ( Figure 1 c). Higher TS levels resulted in more solid particles in the system, which resulted in an increase in the number of intermolecular interactions and the formation of a stronger network structure, thus leading to a higher storage modulus [ 54 ]. Further, it can be observed that the higher loss modulus was also exhibited by 16-A than 12-A ( Figure 1 d).…”
Section: Resultsmentioning
confidence: 99%
“…As reported in [12], a 5-15 % admixture of apricot and pumpkin seed caused a rise in the wheat dough viscosity, similarly to the effect of natural and alkalized cacao found in our investigation. An influence of the additives' components extracted from cacao or carob on the dough viscosity that acts through strengthening/weakening of its structure can be proven by comparison with the constant viscosity increase in a liquid yogurt-like medium containing some carob [13]. Unlike dough, a liquid medium like yogurt does not form any inner structure.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that, rheologically, the structure obtained is similar for dairy products. Additionally, Froiio et al [30] stated that for plant-based, yogurt-like products, these results indicate that the selected matrix is able to represent a stable structure similar to that of dairy yogurt.…”
Section: The Textural Viscosity and Rheological Changesmentioning
confidence: 94%
“…The data were obtained and analyzed by the TA Rheology Advantage Data Analysis equipment software V 5.4.7. (TA Instruments, New Castle, DE, USA) [30].…”
Section: Rheology and Texture Measurementsmentioning
confidence: 99%